Challenging diagnostic for open artery ischemia - Akbar, Akita Rukmana; Rahimah, Anna Fuji (Heart Science Journal, 2025)
Ischemic heart disease has traditionally been linked to obstructive coronary artery disease. However, a significant subset of patients presents with ischemic symptoms despite having non-obstructive coronary arteries—a condition termed Open Artery Ischemia (OAI). This encompasses entities like ANOCA(angina with no obstructive coronary arteries), INOCA(ischemia with nonobstructive coronary arteries), and MINOCA(myocardial infarction with nonobstructive coronary arteries), which challenge conventional diagnostic paradigms.​ Patients with OAI often experience persistent chest discomfort and demonstrable ischemia, yet their angiograms reveal no significant epicardial blockage. These individuals, frequently women in midlife, endure considerable morbidity, including diminished quality of life and recurrent hospitalizations. Underlying mechanisms such as microvascular dysfunction, vasospasm, and systemic inflammation contribute to their symptoms.​ This review aims to elucidate the clinical features, pathophysiological mechanisms, and diagnostic challenges of OAI. By highlighting the importance of advanced diagnostic tools and a patient-centered approach, we advocate for increased awareness and better management strategies for this often-overlooked condition.